Ectopic pregnancy: Medical treatment - Huamán Guerrero, Moisés (2015)
Objective: To evaluate the use of methotexate (MTX) in the treatment of non-complicated ectopic pregnancy. design: Observational prospective study. Setting: Instituto Latinoamericano de Salud Reproductiva. Participants: Women with non complicated ectopic pregnancy. Interventions: Between 1998 and 2005, 21 cases had ultrasound diagnosis of less than 30 mm adnexal tumor, absence of embryo activity, absence of clinical and/or ultrasound evidence of internal hemorrage and chorionic gonadotropin beta sub unit (hCG-β) less than 3000 mUI/mL. Three women had only 1 uterine tube; one of them received MTX in 2 occasions. Treatment consisted in a single dose of MTX 1mg/kg IV or PO. Follow-up consisted in weekly-β and ultrasonographic assessment (including Doppler color study). Informed consent was applied. Main outcome measures: Ectopic pregnancy resolution. Results: Nineteen cases (95,2%) showed satisfactory response to the single MTX dose. One more was needed in one case after one week. One case did not respond to MTX and required surgery at the 3rd day. Following the interventions, 9 women (47,4%) reported becoming pregnant again, one of them had recurrent ectopic pregnancy. Conclusions: Methotrexate treatment in selected cases of tubal ectopic pregnancy is a good therapeutic choice. Acceptance to the treatment was good and no significant adverse effects were reported.